Pulmonary blastoma treatment response to anti-PD-1 therapy: a rare case report and literature review - Xie, Yalin; Su, Ning; Li, Chaoxia; Lei, An; Li, Lei; Zou, Jianjun; Cen, Wencang; Hu, Jinxing (Frontiers in Oncology, 2023)
Pulmonary blastoma (PB) is a rare and invasive malignancy of the lungs with a poor prognosis. Although the mainstay treatment of PB is surgery, and radiotherapy and chemotherapy have been reported, no standard therapy exists for patients inoperable in advanced stages. Moreover, little is known about driver mutation status and immunotherapy efficacy. This paper presents a male patient diagnosed with classic biphasic PB using CT-guided lung biopsy pathology and immunohistochemistry. The patient’s symptoms included cough, chest pain, shortness of breath, hemoptysis, and hypodynamia. The primary focus of this paper is to discuss the impact of anti-PD-1 immunotherapy on PB. The patient experienced progression-free survival (PFS) of over 27 months following sintilimab second-line anti-PD-1 therapy. The patient has currently survived for nearly 40 months with a satisfactory quality of life.